Maternal and foetal outcome in elective versus emergency caesarean sections - Gurunule, Amit A.; Warke, Himangi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean delivery is defined as the birth of the foetus through an incision in the abdominal wall (i.e. laparotomy) and the uterine wall (hysterotomy). The purpose was to analyze the maternal and foetal outcome in elective versus emergency caesarean sections retrospectively in a tertiary care centre and to analyze the indications of elective versus emergency caesarean sections. Methods: A retrospective observational study of the cases undergoing caesarean sections in KEM hospital, Mumbai, India was carried out during the period of September 2013 to September 2015. Maternal and foetal outcome was studied. The data was collected and analyzed from the maternal medical records. The neonatology records were also examined. Results: Out of the 600 selected patients, 300 patients in each group of elective and emergency caesarean section were studied. The usual indications of emergency caesarean sections were foetal distress, followed by meconium stained amniotic fluid (MSAF) and cephalopelvic disproportion (CPD). The most frequent indicator for elective lower segment caesarean section (LSCS) was patient with previous LSCS not willing for vaginal birth, followed by breech presentation and previous multiple LSCS. There was a significant difference seen in the occurrence of fever, urinary tract infections and wound infections in the two groups. These were more common in the emergency caesarean section group. Significant difference was also seen in the incidence of postpartum haemorrhage in the two groups, which was more in the elective caesarean section group. Conclusions: The maternal morbidity, intra operative and postoperative complications were more in the emergency LSCS group as compared to patients who underwent elective LSCS.